Molecular phylogeny of Cremolobus (Brassicaceae) supports the recognition of the new genus Yunkia and demonstrates the high habitat diversity of tribe Cremolobeae. Issue 3 (2nd April 2020) - Salariato, Diego L.; Cano, Asunción; Zuloaga, Fernando O.; Al-Shehbaz, Ihsan A.
Abstract : Cremolobus is a genus of seven species distributed along the Andes from northern Argentina and Chile northward into Colombia, and it inhabits a variety of different environments from humid habitats, such as the Yungas in Bolivia and Argentina or the Andean Paramos in Colombia and Ecuador, to the arid regions of the Sechura Desert in Peru. This genus, together with Aimara and Menonvillea, form the South American tribe Cremolobeae, which is morphologically defined by the indehiscent and 1-seeded schizocarpic silicles. To date, phylogenetic analyses in the tribe were mainly focused on Menonvillea and Aimara, but there are no prior studies on Cremolobus . In this paper, we first studied the phylogenetic placement of Cremolobus within Cremolobeae using ribosomal nuclear (ITS) and chloroplast ( trnL-F, trnH-psbA, rps16 intron) data, including a comprehensive sampling of taxa. We also analysed morphological variation among species, emphasizing habitat adaptation and characterizing main lineages within the genus. Additionally, we studied the biome/habitat preference by the species and main lineages of Cremolobus and other members of the tribe, as well as characterized their climatic niches along the environmental space. Results from our analyses support the monophyly of Cremolobus excluding C. subscandens and C. bolivianus, which are transferred here to the new genus Yunkia . Furthermore, species of Cremolobeae inhabit a wide diversity of habitats along the Andes that are associated with high ecomorphological diversity and, therefore, differing in this aspect from the related tribes Eudemeae and Schizopetaleae. Climatic niche comparison recovered low niche overlap between main lineages of the tribe, but high similarity among species of the same lineage, suggesting the presence of phylogenetic niche conservatism in the tribe. Systematic implications of these results, including a key distinguishing Yunkia from the remaining genera of Cremolobeae and a synopsis of its species, are also provided.